BRST-BFV analysis of anomalies in bosonic string theory interacting with background gravitational field - Buchbinder, I.L.; Mistchuk, B.R.; Pershin, V.D. (Physics letters. B, 1995)
A general BRST-BFV analysis of the anomaly in string theory coupled to background fields is carried out. An exact equation for the c-valued symbol of the anomaly operator is found and the structure of its solution is studied.